Research progress of Traditional Chinese Medicine characteristic nursing techniques for patients with pancreatic cancer (中医特色护理技术在胰腺癌中的应用研究进展) - GAO Donghua (高冬华); WANG Guiting (王贵婷); ZHANG Xinhui (张鑫辉); TIAN Wanqin (田婉琴); Tang Ling (唐玲) (Association of Integrative Nursing, 2021)
Pancreatic cancer is a kind of digestive tract tumor, with a high degree of malignancy. Its clinical manifestations are mainly abdominal discomfort and dull pain, often accompanied by loss of appetite, loss of body shape and obstructive jaundice. With the progress of the disease, the quality of life, work and survival of patients are seriously affected. This article reviewed the etiology and pathogenesis of pancreatic cancer, the characteristics of Traditional Chinese Medicine nursing technology, and its prospects in alleviating pain, improving the quality of life and prolonging the survival time of patients. (胰腺癌是常见的消化道肿瘤, 起病隐匿, 恶性程度高, 严重影响患者生存质量。中医特色护理技术在缓解疼痛、调节情绪、改善症状、提高生活质量等方面具有明显的优势。本文总结了耳穴贴压、穴位注射、艾灸、穴位贴敷等中医特色护理技术在胰腺癌中的应用现状, 旨在为进一步提高胰腺癌患者生存质量提供参考。)